Enhancing Organizational Capacity of Regional Disaster Management Agencies (BPBD) for Effective Disaster Response in Bandung Regency - Nurasa, Heru; Puspita, Dian Permata; Komara, Syifa Rachmania; Karlina, Nina; Pancasilawan, Ramadhan; Yusuf, Farida Nuraeni (Journal of Ecohumanism, 2025)
Bandung Regency is an area prone to natural disasters. The Regional Disaster Management Agency (BPBD) of Bandung Regency needs to enhance its organizational capacity, as it serves as the primary government organization responsible for disaster management. This study employs a qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The development of institutional capacity at BPBD Bandung Regency in disaster management is hindered by several factors, including a lack of transportation facilities and infrastructure, such as mobile toilets, disaster victim transport vehicles, and specialized equipment. Additionally, the agency faces challenges in human resources, as the personnel lack expertise in disaster management, while the budget to support operations remains limited. Furthermore, there is a need to strengthen cooperation with other institutions to achieve common goals. Other obstacles in enhancing BPBD’s institutional capacity include overlapping regulations, which create ambiguity in implementing disaster response, and suboptimal organizational support from personnel. Based on the data analysis, it can be concluded that BPBD Bandung Regency requires significant improvement in its institutional capacity for disaster management. This can be achieved by fostering partnerships with the private sector, collaborating on human resource training, and enhancing direct supervision of operations.